2015
DOI: 10.7448/ias.18.7.20258
|View full text |Cite
|
Sign up to set email alerts
|

The physical and psychological effects of HIV infection and its treatment on perinatally HIV‐infected children

Abstract: IntroductionAs highly active antiretroviral therapy (HAART) transforms human immunodeficiency virus (HIV) into a manageable chronic disease, new challenges are emerging in treating children born with HIV, including a number of risks to their physical and psychological health due to HIV infection and its lifelong treatment.MethodsWe conducted a literature review to evaluate the evidence on the physical and psychological effects of perinatal HIV (PHIV+) infection and its treatment in the era of HAART, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 281 publications
(250 reference statements)
3
58
1
1
Order By: Relevance
“…Prior studies of young children with PHIV described lower mean developmental scores including motor scores among PHIV children compared to PHEU . Our results indicate that only PHIV children with later ART initiation, at three to twelve months of age, had significantly lower general developmental score than PHEU at study enrolment.…”
Section: Discussionsupporting
confidence: 37%
“…Prior studies of young children with PHIV described lower mean developmental scores including motor scores among PHIV children compared to PHEU . Our results indicate that only PHIV children with later ART initiation, at three to twelve months of age, had significantly lower general developmental score than PHEU at study enrolment.…”
Section: Discussionsupporting
confidence: 37%
“…Das et al [27] reported that among the HIV positive adolescents, 45.3 percent K. Lyambai, L. Mwape suffer from psychiatric-morbid constituting emotional disorder (41.7%), conduct disorder (37.5%), somatization (33.3%) and learning-disorder (29.2%). A review of eight studies by Vreeman et al [28] on the prevalence of psychiatric disorders amongst HIV-infected children and youth (aged 4 to 21 years) using the DSM-IV found high rates of anxiety (24%) and depression (25%).…”
Section: Mental Health Problemsmentioning
confidence: 99%
“…Children who are infected with HIV/AIDS face life-long risk of related illnesses, and are more likely to experience cognitive and motor development delays, stigma, trauma, and low mood (Vreeman et al 2015, Abubakar et al, 2008; Sherr et al, 2009). Children who have lost one or both parents to HIV are at increased risk of mental health problems (Mutumba et al 2016, Stein et al 2014, Sherr et al 2014), such as internalising disorders and post-traumatic stress (Cluver & Gardner, 2007), and are often living in alternative care situations.…”
Section: Introductionmentioning
confidence: 99%